Unravelling the Role of the Pentafluoroorthotellurate Group as a Ligand in Nickel Chemistry. Issue 63 (8th September 2022) - Pérez‐Bitrián, Alberto; Hoffmann, Kurt F.; Krause, Konstantin B.; Thiele, Günther; Limberg, Christian; Riedel, Sebastian
Abstract: The pentafluoroorthotellurate group (teflate, OTeF5 ) is able to form species, for which only the fluoride analogues are known. Despite nickel fluorides being widely investigated, nickel teflates have remained elusive for decades. By reaction of [NiCl4 ] 2− and neat ClOTeF5, we have synthesized the homoleptic [Ni(OTeF5 )4 ] 2− anion, which presents a distorted tetrahedral structure, unlike the polymeric [NiF4 ] 2− . This high‐spin complex has allowed the study of the electronic properties of the teflate group, which can be classified as a weak/medium‐field ligand, and therefore behaves as the fluoride analogue also in ligand‐field terms. The teflate ligands in [NEt4 ]2 [Ni(OTeF5 )4 ] are easily substituted, as shown by the formation of [Ni(NCMe)6 ][OTeF5 ]2 by dissolving it in acetonitrile. Nevertheless, careful reactions with other conventional ligands have enabled the crystallization of nickel teflate complexes with different coordination geometries, i.e. [NEt4 ]2 [ trans‐ Ni(OEt2 )2 (OTeF5 )4 ] or [NEt4 ][Ni(bpyMe2 )(OTeF5 )3 ]. Abstract : The homoleptic [Ni(OTeF5 )4 ] 2− anion has been selectively prepared and arises as an analogue of [NiF4 ] 2−, but featuring the discrete tetrahedral geometry of the heavier halonickelates. This high‐spin complex has enabled the investigation of the electronic properties of the [OTeF5 ] − group in coordination chemistry, showing that it behaves as the fluoride also in ligand‐field terms.